FOOD OF THE SARDINES, SARDINELLA ALBELLA (VAL.) AND S. GIBBOSA (BLEEK.) OF THE MANDAPAM AREA - Sekharan, K V (Indian Journal of Fisheries, 2011)
THAT heterogeneous feeding relationship (Ivlev, 1961) in a sardine may be associated with the progressive development of gill rakers during ontogeny has become evident from the studies on the food of the Pacific sardine, Sardinops caerulea (Scofield, 1934) and the Japanese sardine, Sardinops melanosticta (Tokai Regional Fisheries Research Laboratory, 1960). This aspect has been referred to by other workers also (Larraneta, 1960) but not yet studied properly. A closely related problem is selective feeding, the investigation of which requires simultaneous collections of plankton and sardine samples, as borne out by the studies of Hand and Berner (1959) on the food of the Pacific sardine and of various workers on hsrxmg-Calanus relationship (Gushing, 1955).